Typed letter from Theo. Presser Co. to Emil A. Bertl with envelope - Theodore Presser Co.:::Creator::::::::::::; Bertl, Emil A., 1895-1982:::Contributor:::::::::::: (Philadelphia, 2021)
Typed letter from Theo. Presser Co. to Emil A. Bertl regarding the sale of Beethoven relics (locket of hair and flower from Beethoven's grave), dated January 12, 1917, with envelope.